Motivators for Physical Activity among Ambulatory Nursing Home Older Residents - Yuh-Min Chen; Yueh-Ping Li (The Scientific World Journal)
The purpose of this study was to explore self-identified motivators for regular physical activity among ambulatory nursing home older residents. A qualitative exploratory design was adopted. Purposive sampling was performed to recruit 18 older residents from two nursing homes in Taiwan. The interview transcripts were analyzed by qualitative content analysis. Five motivators of physical activity emerged from the result of analysis: eagerness for returning home, fear of becoming totally dependent, improving mood state, filling empty time, and previously cultivated habit. Research on physical activity from the perspectives of nursing home older residents has been limited. An empirically grounded understanding from this study could provide clues for promoting and supporting lifelong engagement in physical activity among older residents. The motivators reported in this study should be considered when designing physical activity programs. These motivators can be used to encourage, guide, and provide feedback to support older residents in maintaining physical activity.